Role of Negative Pressure Therapy as Damage Control in Soft Tissue Reconstruction for Open Tibial Fractures - Cherubino, Mario; Valdatta, Luigi; Tos, Pierluigi; D'Arpa, Salvatore; Troisi, Luigi; Igor, Pellegatta; Corradi, Federica; Khan, Umraz (Journal of Reconstructive Microsurgery, 2017)
The concept of damage control orthopaedics (DCO) is a strategy that focuses on managing orthopaedic injuries in polytrauma patients who are in an unstable physiological state. The concept of DCO is an extension of damage control surgery or damage limitation surgery (DCS/DLS). Recently, it has become clear that certain patients, following extensive soft tissue trauma, could benefit from the idea of DCS. In the management of severe lower extremity trauma with exposed fracture sites, aggressive early wound excision debridement, early internal fixation, and vascularized wound coverage within a few days after trauma were proposed. A negative-pressure dressing can be easily and rapidly applied to obtain a temporary closure between surgical stages. While negative pressure wound therapy (NPWT) has clear indications in the management of chronic wounds, its applications in the acute setting in victims of polytrauma are uneven. We conducted a review of the current clinical literature to evaluate the role of NPWT in this field, which points out that the negative pressure, applied immediately after the first debridement, seems to be an optimal bridge to the final reconstruction up to 7 days.
Keywords: damage control; negative pressure wound therapy; limb trauma; soft tissue; microsurgical reconstruction